2022
DOI: 10.3389/fimmu.2022.1025343
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 autoimmune hepatitis: Genetic susceptibility

Abstract: Two types of autoimmune hepatitis (AIH) are recognized; AIH-1 is characterized by the presence of anti-nuclear and/or anti-smooth muscle autoantibodies, while AIH-2 is associated with the presence of anti-Liver kidney microsome and/or anti-Liver Cytosol antibodies. The autoantigens targeted by AIH-2 autoantibodies are the cytochrome P450 2D6 and Formiminotransferase-cyclodeaminase for anti-LKM1 and anti-LC1 respectively. Both autoantigens are expressed in hepatocytes at higher levels than in any other cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…29 Anti-LC1 has mostly been reported in children and juveniles, and it is mainly associated with anti-LKM-1 reactivity. 9,12,30 However, our research focused on adult patients with liver disorders by excluding juveniles. Considering the scarcity of studies on anti-LC1 in the Asian population, our study investigated a Chinese population to reveal low prevalence of anti-LC1 in Chinese patients (2.42%, 214/8838), which was higher than the reported study (0.16%, 38/23 832), 10 and the difference in the results may be explained by population differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Anti-LC1 has mostly been reported in children and juveniles, and it is mainly associated with anti-LKM-1 reactivity. 9,12,30 However, our research focused on adult patients with liver disorders by excluding juveniles. Considering the scarcity of studies on anti-LC1 in the Asian population, our study investigated a Chinese population to reveal low prevalence of anti-LC1 in Chinese patients (2.42%, 214/8838), which was higher than the reported study (0.16%, 38/23 832), 10 and the difference in the results may be explained by population differences.…”
Section: Discussionmentioning
confidence: 99%
“…The disease-specificity of anti-LC1 in AIH is considered apparent, since it has not been observed in a large number of patients with other hepatic or extra-hepatic diseases. 11,12 Indeed, anti-LC1 can be detected in HCV infection. A previous study showed that 33% (6/18) of anti-LKM (pos) /HCV (pos) patients tested positive for anti-LC1 compared to 0.83% (1/120) of anti-LKM (neg) /HCV (pos) patients and 0% (0/120) of anti-LKM1 (neg) /HBV (pos) patients, suggesting that anti-LC1 screening may only have application potential for anti-LKM1 (pos) /HCV (pos) patients, given its low prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Patients showing positivity for Anti-LKM/Anti-LC-1 antibody were excluded from our study. We had excluded two such patients from our study (positive for Anti-LKM antibody) as there is different genetic susceptibility for AIH-1 and AIH-2, thus we had enrolled adult Non-type 2 AIH cases ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous factors influence the onset and progression of AIH in children, with high-risk genetic elements playing a pivotal role. Genome-wide association studies (GWAS) have unequivocally linked specific HLA alleles, notably HLA-DRB1 03:01 and HLA-DRB1 07:01, with type 2 AIH [2, 6]. This genetic association underscores the crucial involvement of antigen-presenting cells (APCs) and activated CD4+ T helper cells in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It is a life-threatening inflammatory condition characterized by interface hepatitis and the gradual deterioration of liver tissue due to the immune system's attack, culminating in chronic fibrosis, liver failure, and potentially, mortality [1][2][3]. JAIH predominantly affects girls from infancy through late adolescence [4].…”
Section: Introductionmentioning
confidence: 99%